P242 What is the pre-admission NHS-consultation behaviour of adults with community-acquired pneumonia?. (14th November 2013) - Akhtar, M; Woodhead, M
Abstract : Introduction: Under 75 mortality from respiratory disease is highlighted as a target in the NHS Outcomes Framework. Community-acquired pneumonia (CAP) cases are likely to form a considerable proportion of such deaths. Most CAP deaths occur in hospital, but it is not known whether initiatives to reduce such deaths should be primarily targeted at hospital or alternatively at pre-hospital care. To help address this we set out to identify the pre-admission NHS contact behaviour of adults admitted for CAP. Methods: Adult admissions for CAP to one NHS Trust were prospectively identified between 14 th May and 25 th June 2013. For each case the diagnosis was validated by chest radiograph examination. After written informed consent a structured interview was conducted with each patient. Anonymous data was collected in an Excel spread-sheet and analysed with IBM SPSS 20. Results: Of 83 possible pneumonia cases, 64 were confirmed to have radiographic pneumonia and 44 included in the study (Exclusions: declined - 4; language barrier - 4; immune compromise–5; unable to provide history due to illness or confusion–7). Median age was 73 years and CURB65 distribution was 0–1 (36%), 2 (30%), 3–5 (34%) - similar to the BTS audit population. Only 17 (38%) had had some form of pre-admission NHS contact for this illness, the majority presenting directly to hospital. Pre-admission NHS contacts included GP contact (17, including 9 consultations, 5 telephone contacts, 2 home visits, 1 out-of-hours service), 1 walk-in centre and 1 A & E attendance. 1 case had 3 pre admission NHS contacts. There were no contacts with NHS Direct / 111. Those with sputum production, higher CURB65 scores and longer illness duration were significantly more likely to have had pre-admission NHS contact (Table). Multiple other factors (eg age, ethnicity, having English as first language, weekend admission, distance of home from hospital) were not significantly related to pre-admission behaviour. Conclusions: The majority of admitted adult CAP cases presented directly to hospital, but a significant minority had pre-admission NHS contact. Efforts to reduce CAP mortality should primarily be directed at in-hospital care.